The Response of Contemporary Indonesian Islamic Parties Towards Pluralism - Noor, Firman (Journal of Indonesian Social Sciences and Humanities, 2017)
Religion-based political parties, particularly Islamic parties, are often perceived as being less committed to preserving pluralism in comparison with secular parties. Some people regard them as having hidden agendas which are not proper for Indonesia as a plural country. By exploring the ideals and practical aspects of several major Islamic parties, this article wants to highlight the views and attitudes of these parties’ in relation to political diversity that indicates a real position of pluralism within these parties. To measure the Islamic parties’ commitment on pluralism, this article will explore these issues:(1) the main purpose of party establishment, (2) the concept of the ideal form and foundation of a state, including the vision of Pancasila, (3) attitudes towards minority groups, including non-Muslims, Ahmadiyah, Syiah and any other minority groups, (4) policies related to religious concerns, including rights to religious education, the establishment of Islamic Syariah at the local level, and radicalism and (5) developments of political cooperation with secular and non-Muslim parties. The discussion will also touch upon the reasons behind the response towards pluralism as well as addressing the question on whether the response towards pluralism is based on pragmatic interests or Islamic idealism. Discussions about the Islamic parties will also reveal the gradation and level of commitment of the Islamic Parties to pluralism, which in general tend to be supportive towards pluralism.